Identification of Leaf Spot Diseases in Eggplant Using Gray Level Co-Occurrence Matrix (GLCM) Feature Extraction and Support Vector Machine (SVM) Classification - Pahlevi, Reza; Setiawan, Andika; Kesuma, Rahman Indra (Media of Computer Science, 2025)
Eggplant (Solanum melongena L.) is one of the widely cultivated vegetables in Indonesia, belonging to the Solanaceae family. This plant is susceptible to several diseases, one of which is leaf spot disease. Leaf spot disease, caused by the pathogenic fungus Alternaria sp., is characterized by irregularly shaped brown spots with a diameter of approximately 0.5 cm. To address this issue, a digital image processing-based system was developed to identify whether the plant is infected. The proposed system employs feature extraction using the Gray Level Co-Occurrence Matrix (GLCM) combined with the Support Vector Machine (SVM) classification algorithm. The study utilized a dataset of 100 images for training and 50 images for testing. The highest achieved accuracy was 100%, obtained by applying Laplace of Gaussian (LoG) edge detection along with Linear Kernel and Polynomial Kernel SVM classifiers.